PERAN GURU PENDIDIKAN AGAMA ISLAM DAN SUMBER BELAJAR DALAM MENGATASI KESULITAN MEMBACA AL-QURAN PADA SISWA - Imam Hanafi; Ummah Karimah; Siti Shofiyah; Sa’diyah Sa’diyah (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
This article explains the role of Islamic religious education teachers, one of which is in overcoming students' difficulties in reading the Quran. The role of the Islamic education teacher as a learning resource is intended so that students make the teacher a figure who is able to answer all questions asked by students. Another purpose of this research is to find out the role of Islamic education teachers as a portrait in the world of education, where teachers are able to play a role as a learning resource, especially in the problem of difficulty reading the Quran. This research uses a qualitative approach and descriptive type with case study method. The main data sources in this study are Islamic religious education teachers and students. While the secondary data sources are journals, e-books, printed books and so on that are directly related to this research. Data collection techniques using interviews, observation, and document examination. The data validity check uses credibility by extending participation, increasing persistence in research and triangulation. The results of the research findings show that the role of Islamic religious education teachers as a learning resource in overcoming students' difficulties in reading the Quran is that teachers master the material in depth, carry out learning strategies and methods, are able to answer student questions and have references to teaching materials.